Exploring communication between parents and clinical teams following children's heart surgery: a survey in the UK. Issue 1 (22nd March 2019) - Pagel, Christina; Bull, Catherine; Utley, Martin; Wray, Jo; Barron, David J; Stoica, Serban; Tibby, Shane M; Tsang, Victor; Brown, Katherine L
Abstract : Objective: To explore communication between clinicians and families of children undergoing heart surgery. Design: This study was part of a larger study to select, define and measure the incidence of postoperative complications in children undergoing heart surgery. Parents of children recruited to a substudy between October 2015 and December 2017 were asked to complete a questionnaire about communication during their child's inpatient stay. We explored all responses and then disaggregated by the following patient characteristics: presence of a complication, length of stay, hospital site, ethnicity and child's age. This was a descriptive study only. Setting: Four UK specialist hospitals. Results: We recruited 585 children to the substudy with 385 responses (response rate 66%). 81% of parents reported that new members of staff always introduced themselves (18% sometimes, 1% no). Almost all parents said they were encouraged to be involved in decision-making, but often only to some extent (59% 'yes, definitely'; 37% 'to some extent'). Almost two-thirds of parents said they were told different things by different people which left them feeling confused (10% 'a lot'; 53% 'sometimes'). Two-thirds (66%) reported that staff were definitely aware of their child's medical history (31% 'to some extent'). 90% said the operation was definitely explained to them (9% 'to some extent') and 79% that they were definitely told what to do if they were worried after discharge (17% 'to some extent'). Parents of children with a complication tended to give less positive responses for involvement in decision-making, consistent communication and staff awareness of their child's medical history. Parents whose children had longer stays in hospital tended to report lower levels of consistent communication and involvement in decision-making. Conclusions: Our results emphasise the need for consistent communication with families, particularly where complications arise or for children who have longer stays in the hospital.